A336 PREVALENCE AND RISK FACTORS FOR TRANSIENT NEONATAL CHOLESTASIS IN A MOTHER AND CHILD TERTIARY UNIVERSITY CENTER. (1st March 2018) - Chartier, M; Paganelli, M; Alvarez, F
Abstract: Background: Neonatal cholestasis has an incidence of 1/2500 in term infants and can be caused by various disorders. Since the list of genetic diseases associated with neonatal cholestasis is continuously expanding, it is thought that transient neonatal cholestasis (TNC) is decreasing. TNC is characterized by an early onset cholestasis, normalisation of clinical and biochemical parameters at follow-up, and has been associated with neonatal adverse events. Aims: The primary objective was to determine the prevalence of diverse disorders causing neonatal cholestasis and particularly TNC, in our Mother and Child Hospital in Montreal. The secondary objective was to determine if there were factors that could predict the diagnosis of TNC over other diagnosis for cholestasis. Methods: This was a retrospective study that included all patients born between January 1, 2011 and December 31, 2013, who presented with cholestasis in the first 90 days of life. All data were obtained from an electronic neonatal database and through medical chart review. Results: 113 patients were diagnosed with neonatal cholestasis during the 3-year study period. Of those, 74 (64%) had a diagnosis of TNC, 3 (3%) had an obstructive cause (biliary atresia, non-syndromic paucity of bile ducts), 9 (8%) had an infection (TORCH, pyelonephritis), 4 (4%) had a metabolic disorder (galactosemia, cystic fibrosis, Dubin-Johnson), 1 (1%) had an endocrine cause (panhypopituitarism), 2 (2%) had a tumor (liver infiltration of juvenile myelomonocytic leukemia, hemangioendothelioma), 3 (3%) had inspissated bile syndrome from severe hemolysis, 1 (1%) had alloimmune liver disease and 16 (14%) died before the cholestasis was resolved or before the etiologic evaluation was completed. The prevalence of neonatal cholestasis in our NICU was 2.4% and the prevalence of TNC was 1.5%. The majority of patient with TNC had ≥2 risk factors compared to the group with other combined causes for cholestasis; prematurity < 32 weeks in 55% vs 0% (p=<0.0001), parenteral nutrition > 7 days in 82% vs 26% (p=<0.0001), NEC in 23% vs 0% (p=0.0099) and sepsis in 47% vs 22% (p=0.0323) respectively. The mean maximum total bilirubin was lower in the TNC group compared to the group with other causes for cholestasis; 128 umol/L vs 256 umol/L respectively (p=0.008). The average duration of cholestasis was 82 days in the TNC group compared to 85 days in the group with other causes for cholestasis (p=0.8849). However in the latter group, the duration was variable according to the etiology. Conclusions: This study highlights that in a large mother and child hospital, the most likely etiology for cholestasis in infants under the age of 90 days, is TNC, despite advances in diagnostic techniques for metabolic and genetic disorders. This can be explained by the high-risk pregnancies being followed at this tertiary hospital. Funding Agencies: None